A saga king in a Finnish Beijing opera - Kendra Willson (De Gruyter, 2022)
Sigurd Ring, a 2016 Finland-Swedish Peking opera based on a legendary 8th c. king known from 13th c. sagas, presents an example of translation across media and cultures. Elias Edström's debut as director and playwright, following studies at the National Academy of Chinese Theater Arts, is freely adapted from Erik Johan Stagnelius' early 19th c. Romantic play Sigurd Ring: Sorgspel, which in turn was loosely based on saga sources. The modern fusion of two different ancient traditions highlights parallels between the conventions of the source genres. Both show restrained and stylized expressions of emotion; both have clear formulae for character introductions and pacing that varies from very slow set up to intense battle scenes. Typical verbal features of 13th c. Scandinavian texts are translated into the movement and music of Chinese theater. In some ways the modes of expression of the formal Peking opera are closer to the saga ethos than to the Romantic intermediary.
The Vikings reimagined. Reception, recovery, engagement